Virtual empathy as digital competence in education 3.0 - García-Pérez, Rafael; Santos-Delgado, Juan Manuel; Buzón-García, Olga (International Journal of Educational Technology in Higher Education, 2017)
The social and interactive dimension has taken on particular relevance with the appearance of new technologies in education, making the capacity for virtual empathy a key competence for promoting learning processes in virtual environments. Therefore, we conducted a study based on a survey with 704 students who were training as teachers, to whom we applied an adaptation of the empathy scale designed by Gorostiaga et al. (Revista de Educacion 364, 12-38, 2014). The study shows a valid and reliable measure of virtual empathy. Results indicate that only 10 % of the sample reached a high level of virtual empathy and, for this reason, we believe it should be included in teacher education syllabuses.
Keywords: virtual empathy; digital competence; teacher education; web 2.0 technologies; social networks; Emerging; Scopus